Efecto de la posición de soldeo en la soldabilidad de barras corrugadas de acero astm a 615 - Ulloa Vásquez, Wilder Santiago (2018)
The effect of the preheating temperature and welding position on the weldability of steel rebars ASTM A 615 was studied, the joining was carried out by manual electric arc welding process. The weldability was evaluated according to the requirements established in the ANSI / AWS code D1.4-2005 of the American Welding Society, which establishes as the quality limit in this type of steel, minimum tensile strength greater than or equal to 520 Mpa and hardness in the area affected by heat less than 350 HV. The results of 18 specimens under study show that there is a significant effect of the preheating temperature and welding position on the weldability of the ASTM A 615 steels. ASTM A 615 steel has poor weldability when welding without preheating and has good weldability when welding is done preheating to 90 oC in welding position 1G and 2G, the same effect is observed when preheating to 150 oC, in position 1G .